PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN MEMBELI YANG DIMEDIASI OLEH NILAI PELANGGAN PADA RUMAH MAKAN KAMPUNG BAKAU DI KOTA KENDARI: The Influence Of Service Quality And Product Quality On Purchase Decisions Mediated By Customer Value In Kampung Bakau Restaurants In Kendari City - Muhamad Praga Kamaludin; Murdjani Kamaluddin; Noval Nur (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
AbstractThis study aims to examine and explain 1) the effect of service quality on customer value. 2) the influence of service quality on purchasing decisions. 3) the influence of product quality on customer value. 4) the influence of product quality on purchasing decisions. 5) the influence of customer value on buying decisions. 6) the influence of service quality on purchasing decisions mediated by customer value. 7) the influence of product quality on purchasing decisions mediated by customer value. This type of research is a quantitative approach using survey research methods. The number of samples used in this study were 21 indicators x 5 = 105 samples. The technique used in selecting the sample using accidental sampling technique. The results showed that 1) Service Quality had a positive and significant effect on customer value. 2) Service quality has a positive and significant effect on purchasing decisions. 3) Product quality has a positive and significant effect on customer value. 4) Product quality has a positive and significant effect on purchasing decisions. 5) Customer value has a positive and significant effect on buying decisions. 6) Service quality has a positive and significant effect on purchasing decisions through customer value. 7) Product quality has a positive and significant effect on purchasing decisions through customer value.Keywords: service quality, product quality, customer value, and purchasing decisions.